Importance of coverage and quality for impact of nutrition interventions delivered through an existing health programme in Bangladesh - Nguyen, Phuong Hong; Frongillo, Edward A.; Sanghvi, Tina; Kim, Sunny S.; Alayon, Silvia; Tran, Lan Mai; Mahmud, Zeba; Aktar, Bachera; Menon, Purnima (Wiley Online Library, 2022)
This article was published in the Maternal & Child Nutrition [© 2018 The Authors. Maternal and Child Nutrition Published by John Wiley & Sons, Ltd. ] and the definite version is available at : https://doi.org/10.1111/mcn.12613 The Journal's website is at: https://onlinelibrary.wiley.com/doi/10.1111/mcn.12613